Brown Sahib - "Vittachi ,Tarzie" (London, 1962)
This book covers the following topics TWO MEN AND A MOVEMENT; BACK IN BUSINESS;THE OFF-WHITE BLIMP;THE BLACK KNIGHT;THE BROWN SAHIB; OLD MACHINES FOR NEW JOBS NECK DEEP IN 'OUR GLORIOUS HERITAGE';THE ASIAN JINGO; DOWN WITH THE WEST;DIPLOMATIC CIRCUS;ALMS, FOR THE LOVE OF ASIA;GOVERNMENT OF THE PEOPLE, BY SOME People etc.
Keywords: Political Sahib